2013
DOI: 10.26719/2013.19.6.520
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and outcome of childhood asthma: a clinical study in an Egyptian university medical centre

Abstract: The prevalence of childhood asthma has increased recently. The aim of this study was to assess the epidemiology of asthma and risk factors for hospital admission among children attending the outpatient and emergency clinic in a university hospital in Sohag, Egypt. The prevalence of asthma over a 6-month period among children aged 3-12 years at this hospital was 1.4% (178/12 612). All the asthmatic children were enrolled in an observational, prospective questionnaire study. More of the asthmatics were males, li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
3
5
0
Order By: Relevance
“…In our study, cough and dyspnea were the most frequent symptoms of bronchial asthma exacerbation. This was in agreement with others [24,44].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In our study, cough and dyspnea were the most frequent symptoms of bronchial asthma exacerbation. This was in agreement with others [24,44].…”
Section: Discussionsupporting
confidence: 82%
“…El-Hefny [5] found that asthma prevalence was 8.2%, using a questionnaire among 13028 children 3-15 years old. Regarding upper Egypt, the prevalence of questionnaire-diagnosed asthma in two governorates were 6.2% in Assiut district [23] and 1.4% in Sohag district [24]. This difference may be due to the different geographical, social and environmental factors between these two localities.…”
Section: Discussionmentioning
confidence: 99%
“…In Egypt, asthma prevalence in children in the early months of the year (January‐February; 2.0–1.9%) was higher than latter months (May‐June; 1.1–1.3%), in rural residence more than urban residence and in younger more than older children . Family history of allergy and bad housing were also documented as risk factors associated with prevalence of asthma in Egypt .…”
Section: Resultsmentioning
confidence: 95%
“…This will help address and eliminate modifiable risk factors and improve the overall health of children with asthma. 32 low risk high risk low risk NR low risk Rabinovitch et al 33 low risk low risk high risk NR low risk Radic et al 34 low risk high risk high risk NR low risk Lawson et al 35 low risk low risk low risk NR high risk Gerald et al 36 low risk high risk low risk NR low risk Forbes et al 37 low risk low risk low risk NR high risk Vargas et al 38 low risk high risk low risk NR high risk Wang et al 39 low risk high risk high risk NR high risk Murray et al 40 low risk high risk high risk NR high risk Everhart et al 41 low risk high risk low risk NR low risk Cinar et al 42 low risk high risk high risk NR low risk Yamasaki et al 43 low risk high risk high risk NR high risk Jin et al 44 low risk high risk low risk NR low risk Chilmonczyk et al 45 low risk low risk NR NR high risk Abd Elmoneim et al 46 low risk high risk NR NR high risk Lang et al 47 low risk high risk low risk NR low risk Azizi et al 48 low risk high risk low risk NR high risk Ehrlich et al 49 low…”
Section: Discussionmentioning
confidence: 99%